Identification and expression analysis of IL-2 receptors in large yellow croaker (Larimichthys crocea) - Pengfei Mu; Jieying Huo; Min Sun; Xinhua Chen; Jingqun Ao (Fish and Shellfish Immunology Reports, 2021)
Interleukin-2 (IL-2) signals influence various lymphocyte subsets during differentiation, immune responses and homeostasis. IL-2 acts on different cells by binding to its receptors (IL-2R), which consists of three subunits, IL-2Rα (CD25), IL-2Rβ (CD122), and the common gamma chain or γc (CD132). In the present study, three IL-2 receptor subunits, designated as LcCD25-like (LcCD25L), LcIL-2Rβ and Lcγc, were characterized in large yellow croaker (Larimichthys crocea). The LcCD25L, like other teleost CD25L or IL-2/IL-15Rα, contains only one sushi domain at N-terminus. The synteny of CD25L from different teleost are conserved. The deduced protein of LcIL-2Rβ and Lcγc exhibits a typical class I cytokine receptors architecture, including a cytokine-binding homology domain (CHD) consisting of two fibronectin type-III (FNIII) domains (D1 and D2) and a conserved WSXWS motif in D2 domain. These three IL-2 receptor subunits were constitutively expressed in all tissues and primary immune-related cells examined. The LcCD25L was highly expressed in blood, while LcIL-2Rβ and Lcγc were highly expressed in spleen and gill. For immune-related cells, LcCD25L and LcIL-2Rβ were highly expressed in PKLs, while the Lcγc exhibited the highest expression in PKMs. These three IL-2 receptor subunits could be dramatically induced by T cell mitogen PHA in PKLs, which mainly composed of T and B lymphocytes. The results presented indicated that large yellow croaker IL-2R might exercise function on lymphocytes, especially on activated T cells.